Overlapping Phenotypes Associated With CYP24A1, SLC34A1, and SLC34A3 Mutations: A Cohort Study of Patients With Hypersensitivity to Vitamin D - Molin, Arnaud; Lemoine, Sandrine; Kaufmann, Martin; Breton, Pierre; Nowoczyn, Marie; Ballandonne, Céline; Coudray, Nadia; Mittre, Hervé; Richard, Nicolas; Ryckwaert, Amélie; Lavillaureix, Alinoe; Jones, Glenville; et al. (Frontiers in Endocrinology, 2021)
Mutations in CYP24A1 (vitamin D 24-hydroxylase) and SLC34A1 (renal phosphate transporter NPT2a) cause autosomal recessive Infantile Hypercalcemia type 1 and 2, illustrating links between vitamin D and phosphate metabolism. Patients may present hypercalciuria and alternate between chronic phases of normocalcemia with inappropriately high 1,25-(OH)2D and appropriately low PTH, and acute phases of hypercalcemia with suppressed PTH. Mutation in SLC34A3 and SLC9A3R1 have been associated with phosphate wasting without hypercalcemia. The aims of this study were to evaluate the frequency of mutations in these genes in patients with a medical history suggestive of CYP24A1 mutation to search for a specific pattern. Using next generation sequencing, we screened for mutations in 185 patients with PTH levels < 20 pg/mL, hypercalcemia and/or hypercalciuria, and relatives. Twenty-eight (15%) patients harbored biallelic mutations in CYP24A1 (25) and SLC34A3 (3), mostly with renal disease (lithiasis, nephrocalcinosis) (86%). Hypophosphatemia was found in 7 patients with biallelic mutations in CYP24A1 and a normal phosphatemia was reported in 2 patients with biallelic mutations in SLC34A3. Rare variations in SLC34A1 and SLC34A3 were mostly of uncertain significance. Fifteen patients (8%) carried only one heterozygous mutation. Heterozygous relatives carrying SLC34A1 or SLC34A3 variation may present with biochemical changes in mineral metabolism. Two patients’ genotype may suggest digenism (heterozygous variations in different genes). No variation was found in SLC9A3R1. As no specific pattern can be found, patients with medical history suggestive of CYP24A1 mutation should benefit from SLC34A1 and SLC34A3 analysis.